Analisis Kepuasan Pengguna Simponi Mobile pada Universitas XYZ Dengan Metode End User Computing Satisfaction (EUCS) - Lisa Amelia Fransen; Dorie Pandora Kesuma (Buletin Ilmiah Informatika Teknologi, 2023)
The use of academic information systems in higher education today has become a necessity that cannot be ignored. Academic information systems in tertiary institutions can be said to be the heart that has an important role in improving performance and also serving its users. XYZ University has developed a Simponi Mobile application which is used by students to find out information related to lectures. To find out the level of user satisfaction of the Simponi Mobile application, the authors want to examine whether the Simponi Mobile application has provided satisfaction to its users, namely students using the End User Computing Satisfaction (EUCS) method. Based on the results of the Likert scale assessment, it can be concluded that the five EUCS dimensions used in this study produced an average index value of 88.47% for the Content dimension, 85.22% for the Accuracy dimension, 86.16% for the Dimension Format, 86.74% for the Timeliness dimension, and 87.84% for the Ease of Use dimension. From these results, it can be seen that the results of measuring the Simponi Mobile application carried out by respondents based on the five dimensions of End User Computing Satisfaction (EUCS) fall into the very satisfied category.